A comparative study of the modeled effects of atrazine on aquatic plant communities in midwestern streams. (6th October 2015) - Nair, Shyam K.; Bartell, Steven M.; Brain, Richard A.
Abstract Potential effects of atrazine on the nontarget aquatic plants characteristic of lower‐order streams in the Midwestern United States were previously assessed using the Comprehensive Aquatic System Model (CASMATZ). Another similar bioenergetics‐based, mechanistic model, AQUATOX, was examined in the present study, with 3 objectives: 1) to develop an AQUATOX model simulation similar to the CASMATZ model reference simulation in describing temporal patterns of biomass production by modeled plant populations, 2) to examine the implications of the different approaches used by the models in deriving plant community‐based levels of concern (LOCs) for atrazine, and 3) to determine the feasibility of implementing alternative ecological models to assess ecological impacts of atrazine on lower‐order Midwestern streams. The results of the present comparative modeling study demonstrated that a similar reference simulation to that from the CASMATZ model could be developed using the AQUATOX model. It was also determined that development of LOCs and identification of streams with exposures in excess of the LOCs were feasible with the AQUATOX model. Compared with the CASMATZ model results, however, the AQUATOX model consistently produced higher estimates of LOCs and generated non‐monotonic variations of atrazine effects with increasing exposures. The results of the present study suggest an opportunity for harmonizing the treatments of toxicity and toxicity parameter estimation in the CASMATZ and the AQUATOX models. Both models appear useful in characterizing the potential impacts of atrazine on nontarget aquatic plant populations in lower‐order Midwestern streams. The present model comparison also suggests that, with appropriate parameterization, these process‐based models can be used to assess the potential effects of other xenobiotics on stream ecosystems. Environ Toxicol Chem 2015;34:2590–2602. © 2015 SETAC